Sistem Rekomendasi Tempat Wisata di Kota Malang Menggunakan Metode Hybrid Fuzzy-Floyd Warshall - Muhamad Danis Firmansyah; Edy Santoso; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tourism has become one of the industry that delivers great results for an area. So the object of tourism need to be developed to get maximum results. There are various influences of the development of tourism, one of which is the improvement of the economy of the community around tourist attractions. Malang is one city that has a variety of tourism and become a popular place for targeted by people who live in East Java in particular. However, because of the many excursions into its own problems for tourists to take a decision. Decision sightseeing recommendations as seen from a variety of factors, such as; ticket prices, distance tour from user location is currently in the form of maps, facilities. Fuzzy logic is a method of determining who can cope with uncertainty, so it will be very helpful in deciding which attractions will be targeted. In addition to assisting in the determination of the closest lanes will use methods of floyd-warshall. So that the process of determining the closest line of maps will be assisted by floyd-warshall and the process of determination of the tour will be visited using fuzzy logic.